Special Issue “Gamma Delta T Cells in Immune Response against Viruses” - Eric Champagne (Viruses, 2022)
γδ T cells are members of ‘unconventional’ T cells that combine the properties of adaptive T lymphocytes and innate cells such as NK cells [...]